A critical review of conscientious objection and decriminalisation of abortion in Chile - Montero, Adela (Journal of medical ethics, 2018)
From 1989 through September 2017, Chile’s highly restrictive abortion laws exposed women to victimisation and needlessly threatened their health, freedom and even lives. However, after decades of unsuccessful attempts to decriminalise abortion, legislation regulating pregnancy termination on three grounds was recently enacted. In the aftermath, an aggressive conservative drive designed to turn conscientious objection into a pivotal new obstacle, mounted during the congressional debate, has led to extensive, complex arguments about the validity and legitimacy of conscientious objection. This article offers a critical review of the emergence of conscientious objection and its likely policy and ethical implications. It posits the need to regulate conscientious objection through checks and balances designed to keep it from being turned into an ideological barrier meant to hinder women’s access to critical healthcare.